Detection of Antimicrobial Resistance Genes in the Milk Production Environment: Impact of Host DNA and Sequencing Depth - Rubiola, Selene; Chiesa, Francesco; Dalmasso, Alessandra; Di Ciccio, Pierluigi; Civera, Tiziana (Frontiers in Microbiology, 2020)
Over the past decades, antimicrobial resistance (AMR) has been recognized as one of the most serious threats to public health. Although originally considered a problem to human health, the emerging crisis of AMR requires a “One Health” approach, considering human, animal and environmental reservoirs. In this regard, the extensive use of antibiotics in the livestock production systems to treat mastitis and other bacterial diseases can lead to the presence of AMR genes in milk and dairy products, thereby introducing them into the food chain. The recent development of high-throughput next generation sequencing (NGS) technologies are improving the fast characterization of microbial communities and their functional capabilities. In this context, whole metagenome sequencing (WMS), also called shotgun metagenomic sequencing, allows the generation of a vast amount of data which can be interrogated to generate the desired evidence, including the resistome. However, the amount of host DNA poses a major challenge to metagenome analysis. Given the current absence of literature concerning the application of WMS on milk to detect the presence of AMR genes, in the present study we evaluated the effect of different sequencing depths, host DNA depletion methods and matrices to characterize the resistome of a milk production environment. WMS was conducted on three aliquots of bulk tank milk and three aliquots of the in-line milk filter collected from a single dairy farm; a fourth aliquot of milk and milk filter was bioinformatically subsampled. Two commercially available host DNA depletion methods were applied, and metagenomic DNA was sequenced to two different sequencing depth. Milk filters proved to be the most suitable matrices to evaluate the presence of AMR genes; besides, the pre-extraction host DNA depletion method was the most efficient approach to remove host reads. To our knowledge, this is the first study to investigate the milk resistome with a WMS approach, evaluating the limitations posed by the host DNA and confirming the circulation of AMR genes in the milk production environment.